The Effect Of Ceo Power On The Selection Of Qualified Auditors With Profitability As Moderator - Feby Astrid Kesaulya; Weny Putri; Khairunnisa (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of CEO Power on the selection of qualified auditors with profitability as a moderator. This study uses a sample of small and medium-sized enterprises listed on the PEFINDO 25 index May 2023, the data used is company data from 2020-2022. Hypothesis testing using logistic regression analysis. The results of the study show that profitability does not moderate the influence of CEO Power on the selection of qualified auditors. The results of this study are expected to increase literacy regarding what factors can influence the selection of auditors. In addition, the CEO of the company also must consider thoroughly when selecting auditors for his/her company in order to maintain the quality of company’s financial reporting.